Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1093/ndt/gfac022
|View full text |Cite
|
Sign up to set email alerts
|

Itching in dialysis patients: impact on health-related quality of life and interactions with sleep problems and psychological symptoms—results from the RENINE/PROMs registry

Abstract: Background Itching (pruritus) is common in dialysis patients, but little is known about its impact on health-related quality of life (HRQOL), sleep problems and psychological symptoms. This study investigates the impact of itching in dialysis patients by looking into the persistence of itching, the effect of itching on the course of HRQOL, and the combined effect of itching with sleep problems and with psychological symptoms on HRQOL. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
(57 reference statements)
1
10
0
Order By: Relevance
“…Second, in contrast, the burden of itch, a classic uremic symptom, did not improve after dialysis initiation. This is in line with previous studies that also found a high burden of itching in patients on dialysis (39,40). This may be partly explained by the fact that dialytic clearance of uremic toxins is limited to the unbound fraction that can diffuse across the dialysis membrane (14,15).…”
Section: Discussionsupporting
confidence: 93%
“…Second, in contrast, the burden of itch, a classic uremic symptom, did not improve after dialysis initiation. This is in line with previous studies that also found a high burden of itching in patients on dialysis (39,40). This may be partly explained by the fact that dialytic clearance of uremic toxins is limited to the unbound fraction that can diffuse across the dialysis membrane (14,15).…”
Section: Discussionsupporting
confidence: 93%
“…A study of RENINE/PROMs registry data of 2978 Dutch dialysis patients by van der Willik et al revealed that 50% of patients had itching which was described as “persistent itching” by 70% of those 50%. 11 …”
Section: Ckd-ap: Importancementioning
confidence: 99%
“… 47 An elevated calcium phosphate product and elevated parathyroid hormone level in the group of patients who benefitted from parathyroidectomy suggests that CKD mineral bone disease may be a factor related to CKD-aP. 11 , 12 However the calcium phosphate product is an artificial construct and unlikely to be highly representative in the complex physiology of mineral trafficking and it is highly likely that the subtleties of mineral trafficking have been missed by the crude association of the calcium phosphate product. Nevertheless, there is more calcium in the basal skin layer in patients with CKD-aP and this is an area that needs further research.…”
Section: Obstacles To the Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic itch generally lasts more than 6 weeks and is often associated with multiple pathological conditions, such as skin diseases, including atopic dermatitis (AD), and other systemic diseases, such as liver and kidney diseases . Chronic itch is a maladaptive and debilitating condition that is accompanied by a host of comorbidities, including depression, insomnia, and anxiety disorders, , which affect the quality of life of millions of patients . In many cases, scratching is not effective in relieving chronic itch. , Moreover, repetitive scratching can lead to skin damage, worsening the itch and leading to further scratching, thereby creating a vicious cycle. However, effective drugs for the treatment of itch, especially chronic itch in clinical settings, are lacking .…”
Section: Introductionmentioning
confidence: 99%